2000
DOI: 10.1007/bf03032360
|View full text |Cite
|
Sign up to set email alerts
|

Intra-tumoral cytolytic cells: Pattern of distribution in B-cell non Hodgkin’s lymphoma

Abstract: Non-Hodgkin s lymphomas (NHLs) constitute a heterogeneous group of lymphoid neoplasms and a majority of them in India are of B-cell phenotype. Varying numbers of T lymphocytes and natural killer (NK) cells are consistently present within the lymph nodes (LNs). The role of these reactive cells is becoming understood. TIA-1 is a cytotoxic granule associated RNA binding protein, the expression of which is restricted to cytotoxic T lymphocytes (CTLs) and NK cells. Snap frozen lymph node biopsies obtained from 41 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…In preliminary experiments, we have shown apoptosis of B‐CLL tumour cells as determined by Annexin V binding by freshly isolated CD4 + T cells through CD3xCD19 bispecific antibodies. Interestingly, there are also now reports of the cytotoxicity‐related molecule TiA by CD4 + as well as CD8 + cells in non‐Hodgkin lymphomas and other lymphomas ([29] and A. Dogan, personal communication), suggesting that they may have a role in other lymphoid malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…In preliminary experiments, we have shown apoptosis of B‐CLL tumour cells as determined by Annexin V binding by freshly isolated CD4 + T cells through CD3xCD19 bispecific antibodies. Interestingly, there are also now reports of the cytotoxicity‐related molecule TiA by CD4 + as well as CD8 + cells in non‐Hodgkin lymphomas and other lymphomas ([29] and A. Dogan, personal communication), suggesting that they may have a role in other lymphoid malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells are important components of the innate immune response against malignant cells. In FL, NK cell amount in peripheral blood is associated with clinical outcomes as low cell number correlates with worse overall survival and shorter time to progression (22, 23). This seems to be correlated with a decrease of RTX mediated ADCC in FL patients (41).…”
Section: Discussionmentioning
confidence: 99%
“…Their low count in the peripheral blood of FL patients is correlated with poor prognosis, strongly supporting their key role for therapy (21, 22). In infiltrated lymph nodes and follicles of FL patients, NK cells are present (23), but their cytotoxic status and the modelization of their function in a relevant FL model are unexplored. We are pioneer in the development of 3D FL in vitro model, called MALC.…”
Section: Introductionmentioning
confidence: 99%
“…Besides cytotoxic effector functions, activated NK cells can produce high levels of cytokines, which may in turn lead to further activation of several immune cell types including T cells (8). Previous studies have shown that cytotoxic lymphocytes predominantly reside at the periphery of follicles and in the interfollicular areas close to T cells (24). In this compartment, the interplay with T cells secreting IL-2 leads to NK cell-mediated release of IFNγ (14).…”
Section: Discussionmentioning
confidence: 99%